2016
DOI: 10.1016/j.jcrysgro.2015.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray topographic study on nature of threading mixed dislocations in 4H–SiC crystals grown by PVT method

Abstract: Synchrotron X-ray Topography is a powerful technique to study defects structures particularly dislocation configurations in single crystals. Complementing this technique with geometrical and contrast analysis can enhance the efficiency of quantitatively characterizing defects. In this study, the use of Synchrotron White Beam X-ray Topography (SWBXT) to determine the line directions of threading dislocations in 4H-SiC axial slices (sample cut parallel to the growth axis from the boule) is demonstrated. This tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Evidently, the size of the dislocation image is larger than those in Figs. 3(a The threading dislocations studied here have a screw component and are either TSDs or TMDs (although it has been shown that the latter are the most significant contributors to the typically observed threading dislocation densities (Guo et al, 2016). According to the g Á b ¼ 0 and g Á b  l ¼ 0 criteria (g is the reflection vector, b the is Burgers vector and l is the dislocation line direction), the edge component of the TMD Burgers vector (b e ¼ 1 3 h11 2 20i) will not significantly contribute to the contrast in 0008 PWT despite the contributions from the effects of surface relaxation (Raghothamachar et al, 2010;Peng, Ailihumaer, Fujie et al, 2021).…”
Section: Dislocation Contrast In Xrtmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidently, the size of the dislocation image is larger than those in Figs. 3(a The threading dislocations studied here have a screw component and are either TSDs or TMDs (although it has been shown that the latter are the most significant contributors to the typically observed threading dislocation densities (Guo et al, 2016). According to the g Á b ¼ 0 and g Á b  l ¼ 0 criteria (g is the reflection vector, b the is Burgers vector and l is the dislocation line direction), the edge component of the TMD Burgers vector (b e ¼ 1 3 h11 2 20i) will not significantly contribute to the contrast in 0008 PWT despite the contributions from the effects of surface relaxation (Raghothamachar et al, 2010;Peng, Ailihumaer, Fujie et al, 2021).…”
Section: Dislocation Contrast In Xrtmentioning
confidence: 97%
“…In regular 1128 GIT or 0 0 0 12 back-reflection topographs, threading screw dislocations (TSDs) and threading mixed dislocations (TMDs) usually show contrast features comprising white ellipses or circles (Huang et al, 2007;Vetter et al, 2005;Guo et al, 2016). For instance, Fig.…”
Section: Dislocation Contrast In Xrtmentioning
confidence: 99%
“…low X-ray energies, and thus accesses mostly information about the crystal regions close to the wafer's surface. However, in transmission topography, assigning TDs to their type is hindered because superscrew dislocations like micropipes (MPs) appear as two short and parallel dark contrast lines, which only give information about their position in the measured topography area (Dudley et al, 1995;Vetter & Dudley, 2006;Guo et al, 2016). Thus, for this work, the back-reflection wafer mappings were used to assign TDs to their type, and transmission topographs were consulted to confirm different dislocation types or to compare the depicted dislocation density.…”
Section: Introductionmentioning
confidence: 99%
“…Dislocations can be classified according to the Burgers vector and line direction and thus major dislocations in 4H-SiC crystals include threading screw dislocations (TSDs) with c-component, threading mixed dislocations (TMDs) with c and a-components, threading edge dislocations (TEDs) having only a-component, and basal plane dislocations (BPDs) having a-component. [2][3][4][5][6][7] The typical densities of TSDs/TMDs, TEDs and BPDs in commercial 4H-SiC substrates, which are sliced from PVT grown bulk crystals, can be 10 2 -10 3 , 10 3 -10 4 and 10 2 -10 4 cm −2 , respectively. Such dislocations in the substrates propagate in epitaxial layers which are used as an active region of the devices and affect the device performances in some cases.…”
mentioning
confidence: 99%
“…Dislocations were classified into TSDs, TMDs, TEDs and BPDs by the pattern of topography defect contrast. [2][3][4][5][6][7] Frank-type dislocations 17,18) on the basal plane, which were contained in the seed crystal and propagated into the grown crystal at an early stage, were excluded from counting. We did not distinguish BPDs and prismatic dislocation 19) in the topography analysis and a small number of prismatic dislocations could be counted as BPDs.…”
mentioning
confidence: 99%